2015
DOI: 10.1016/j.hlc.2015.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Peri-operative Levosimendan in Patients Undergoing Cardiac Surgery: An Overview of the Evidence

Abstract: Levosimendan, a calcium sensitiser, has recently emerged as a valuable agent in the peri-operative management of cardiac surgery patients. Levosimendan is a calcium-sensitising ionodilator. By binding to cardiac troponin C and reducing its calcium-binding co-efficient, it enhances myofilament responsiveness to calcium and thus enhances myocardial contractility without increasing oxygen demand. Current evidence suggests that levosimendan enhances cardiac function after cardiopulmonary bypass in patients with bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…LS application had no significant effect on overall 30-days survival which is on one hand contradictory to previous studies showing positive effects of prophylactic LS on short-term survival [11, 12]. On the other hand, recent meta-analysis of the available data revealed conflicting results on whether or not LS reduces mortality [18, 19]. A differentiated analysis of our patient subgroups showed tendencies towards positive effects of LS on 30-days survival in patients undergoing valve/aortic or combination procedures, patients with moderate chronic renal impairment, patients who had no recent myocardial infarction, patients with LVEF <25% and patients with EuroSCORE II risk estimation scores >23.…”
Section: Discussionmentioning
confidence: 75%
“…LS application had no significant effect on overall 30-days survival which is on one hand contradictory to previous studies showing positive effects of prophylactic LS on short-term survival [11, 12]. On the other hand, recent meta-analysis of the available data revealed conflicting results on whether or not LS reduces mortality [18, 19]. A differentiated analysis of our patient subgroups showed tendencies towards positive effects of LS on 30-days survival in patients undergoing valve/aortic or combination procedures, patients with moderate chronic renal impairment, patients who had no recent myocardial infarction, patients with LVEF <25% and patients with EuroSCORE II risk estimation scores >23.…”
Section: Discussionmentioning
confidence: 75%
“…Levosimendan has been used in the treatment of heart failure (HF) over the past decade. Studies have shown clinical improvement in terms of hemodynamic parameters, cardiac function, shorter overall in-hospital stay, while data for long-term mortality is still controversial [ 23 ].…”
Section: Effects Of Levosimendan In Patients With Heart Failurementioning
confidence: 99%
“…Evidence shows the benefit of coronary surgery over medical treatment in patients suffering from both decreased left ventricular function and coronary artery disease [ 20 , 28 ]. Patients undergoing cardiac surgery with high-risk profile require peri-operative and post-operative inotropic support and levosimedan seems to be an attractive option in such patients [ 23 ]. Different meta-analyses have suggested mortality benefits in patients undergoing cardiac surgery receiving levosimendan.…”
Section: Levosimendan In Cardiac Surgerymentioning
confidence: 99%
See 2 more Smart Citations